The Impact of Foreign Direct Investment on the Growth of the Industrial Sector in the Kingdom of Saudi Arabia during the period (2000-2020) - Shesha, Lamia Saud; Nasurldeen, Vivian; Alhuthali, Nora (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aimed to identify the impact of foreign direct investment on the growth of the industrial sector in the Kingdom of Saudi Arabia during the period (2000-2020), and in order to investigate the relationships, a Multiple Regression Analysis model was described, to express the relationship between the development of the industrial sector as a dependent variable -expressed by manufacturing- and the independent variables related to foreign direct investment, which were selected based on previous studies and researchers’ judgments, represented in the gross fixed capital formation (% of GDP), total number of labor operating industrial units, foreign direct investment net inflows (% of GDP), total number of industrial exports, and open trade. By identifying the variables and hypotheses to be tested, descriptive tests were conducted, and the general trend of the variables was identified, by the statistical program E-views. As expected, the results showed a direct relationship between the dependent variable and all of the gross fixed capital formation (% of GDP) (0.028533), total number of labor operating industrial units (0.179044), foreign direct investment net inflows (% of GDP) (0.012077), total number of industrial exports (0.411151), while it showed -contrary to what was expected- the existence of an inverse relationship between the dependent variable and open trade (-0.013831).